Improving the Quality of Uninhabitable Houses in Kwala Gebang Village, Langkat Regency - Nugroho Dedi Permadi; Abdi Sugiarto; Cut Nuraini (CV. Doki Course and Training, 2026)
This study aims to analyze the physical conditions of uninhabitable houses, identify the factors that constrain communities from improving housing quality, and formulate effective and sustainable strategies for housing improvement in Kwala Gebang Village, Langkat Regency. this research employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. the results show that most houses in Kwala Gebang Village are in poor physical condition, with inadequate ventilation and lighting, as well as insufficient sanitation. the main factors constraining the community in improving housing quality include economic limitations, lack of understanding of habitable housing standards, technical building constraints, and the limited effectiveness of government programs. the impacts of uninhabitable housing are evident in community health, safety, and well-being, including increased risks of disease, accidents, and psychological stress. applicable strategies include improving the targeting of government programs, encouraging active community participation, implementing technical housing improvements, providing community education and empowerment, and conducting continuous monitoring and evaluation. this study is expected to serve as a reference for planning effective, efficient, and sustainable housing improvement programs.